Legal and Victimological Perspective on Sexual Violence against Children Cases in Indonesia - Ilyasa, Raden Muhammad Arvy (The Indonesian Journal of International Clinical Legal Education, 2021)
Every year in Indonesia there are various cases of sexual violence against children whose quantity is increasing every year. Protection of children from all threats of crime that can threaten their survival is contained in the constitution of the State of Indonesia as a country that upholds law and human rights. When children experience incidents of sexual violence, their future will be threatened due to psychological, mental and social trauma factors. Therefore, in this paper, the author wants to examine how to handle cases of sexual violence in Indonesia from a legal and victimological perspective by identifying the problem, namely how is legal protection for children as victims in cases of sexual violence and how is the perspective of victimology in this case the study of victims in acts of violence. crime or crime.